Normalised MRI Volumetry of the Hippocampus among Normal Malay Children and Adolescents - Jalaluddin, Win Mar @ Salmah (Penerbit Universiti Sains Malaysia, 2013)
BACKGROUND: Magnetic resonance imaging (MRI) is a noninvasive method for determining brain morphology and volumetry. Hippocampal volume changes are observed in conjunction with several diseases. This study aimed to determine the normalised volume of the hippocampus in normal Malay children and adolescents. METHODS: This was a cross-sectional study performed from January 2009 to June 2010. Brain and temporal lobe MRI was performed for 81 healthy normal Malay individuals aged 7–18 years. Manual volumetry was performed. The hippocampal volumes were normalised with the total intracranial volume. RESULTS: The original right, left, and total hippocampal volumes (mean and standard deviation) were 3.05 (0.48) cm(3), 2.89 (0.44) cm(3), and 5.94 (0.90) cm(3), respectively. Normalised hippocampal volumes for the right, left, and total volume were 3.05 (0.41) cm(3), 2.89 (0.41) cm(3), and 5.94 (0.79) cm(3), respectively. Pearson’s correlation coefficient for the right and left hippocampal volumes with intracranial volume were 0.514 and 0.413, respectively (P < 0.001). Both the original and normalised hippocampal volumes of the right hippocampus were significantly larger than those of the left (P < 0.001). CONCLUSION: This is a data set for the local Malay paediatric population. There was no significant difference between the actual and normalised values of hippocampal volume in our study.